2010
DOI: 10.1096/fj.10-161851
|View full text |Cite
|
Sign up to set email alerts
|

Role of CCR5 and its ligands in the control of vascular inflammation and leukocyte recruitment required for acute excitotoxic seizure induction and neural damage

Abstract: Chemokines may play a role in leukocyte migration across the blood-brain barrier (BBB) during neuroinflammation and other neuropathological processes, such as epilepsy. We investigated the role of the chemokine receptor CCR5 in seizures. We used a rat model based on intraperitoneal kainic acid (KA) administration. Four months before KA injection, adult rats were given femoral intramarrow inoculations of SV (RNAiR5-RevM10.AU1), which carries an interfering RNA (RNAi) against CCR5, plus a marker epitope (AU1), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 101 publications
3
51
1
Order By: Relevance
“…Chemokine expression is known to influence the seizure outcome in patients with epilepsy. RANTES has been implicated in the recruitment of inflammatory cells to the CNS in the kainic acid seizure model (25). Fiala et al evaluated RANTES expression in temporal lobe epilepsies (TLE).…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine expression is known to influence the seizure outcome in patients with epilepsy. RANTES has been implicated in the recruitment of inflammatory cells to the CNS in the kainic acid seizure model (25). Fiala et al evaluated RANTES expression in temporal lobe epilepsies (TLE).…”
Section: Discussionmentioning
confidence: 99%
“…47 Mononuclear cells (expressed as the number per unit area) were enumerated in HEstained sections of liver and heart in at least five consecutive sections using a computerized imaging system (Image-Pro Plus, MediaCybernetics, Rockville, MD,USA) as previously described. 49,50 CD3-and CD45-positive cells were enumerated on sections of the spleen immunostained with the corresponding antibodies. COX-negative fibers (% of the total number of heart fibers) were counted in heart sections sequentially stained by COX then SDH.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have also reported elevated chemokine receptor expression in the brain tissue of ASD patients [10,11]. Previous research showed that chemokine receptors are also implicated in neuroinflammation, neural damage, and astrocyte proliferation [18]. The expression levels of chemokine receptors were elevated in the temporal cortex of individuals with autism [5].…”
Section: Introductionmentioning
confidence: 94%